Genetic diversity & drug sensitivity profiles of Mycobacterium tuberculosis isolates from two slums of Jaipur city, Rajasthan, India - Bharti Malhotra (Indian Journal of Medical Research, 2017)
Background & objectives: Slums are considered as hotspots of tuberculosis (TB). The study of genetic diversity and drug susceptibility profile of Mycobacterium tuberculosis (MTB) will help understand the transmission dynamics and can be used for better prevention and control of the disease. The aim of this study was to determine the drug susceptibility profiles and genetic diversity using the random amplified polymorphic DNA (RAPD) and mycobacterial interspersed repetitive units-variable number of tandem repeats (MIRU VNTR) of MTB isolates from sputum samples of pulmonary TB patients residing in the two slums of Jaipur city in Rajasthan, India. Methods: Sputum samples collected from pulmonary TB patients, their contacts and suspects during 2010-2012 were processed for microscopy and mycobacterial culture. Drug susceptibility testing was done by one per cent indirect proportion method on Lowenstein–Jensen medium for first-line anti-TB drugs rifampicin, isoniazid, ethambutol and streptomycin. MTB DNA was extracted by physicochemical method, and DNA fingerprinting was done by RAPD and MIRU VNTR analysis. Results: Among 175 sputum samples collected, 75 were positive (43.8%) for acid-fast bacilli, 83 for MTB culture and four were contaminated. Fifty two isolates (62.7%) were fully sensitive to four drugs, and five (6%) were multidrug resistant (MDR). RAPD analysis of 81 isolates revealed six clusters containing 23 (28.4%) isolates, and 58 (71.6%) were unique. MIRU VNTR analysis clustered 20 (24.7%) isolates, and 61 (75.3%) were unique. Interpretation & conclusions: About 62.7 per cent isolates from the sputum samples from slum areas were sensitive to four drugs; six per cent of isolates were MDR. Poly-resistance other than MDR was high (16%). About one-fourth isolates were clustered by either method. RAPD was rapid, less expensive but had low reproducibility. MIRU VNTR analysis could identify to greater extent the epidemiological link in the population studied.